Analisis Permohonan Wali Dan Kuasa Dari Ahli Waris Pemohon Yang Belum Dewasa Guna Untuk Mengambil Jaminan Sertifikat Rumah - Endang Prasetyawati; Indah Satria; Yenita Septiara (CV. Ulil Albab Corp, 2022)
Decision Number: 87/Pdt.P/2021/PN Tjk stipulates that granting the petition of the petitioner, stipulates that Ridwan is legally valid as the guardian of a boy named Jow Orlando born in Pagardin, January 19, 2001 is an immature child and have not been able to act according to law, stipulating Ridwan is the guardian of a child named Jow Orlando for the purpose of registering to a TNI school and charging a case fee arising in this application of Rp. 296,000 (two hundred ninety six thousand rupiah). The problem in this research is what are the factors causing the legal determination of the appointment of a guardian for a child based on Decision Number: 87/Pdt.P/2021/PN Tjk?, what is the legal consequence of the legal determination of the appointment of a guardian for a child based on Decision Number: 87/Pdt.P/2021/PN Tjk? and how is the end of determining the legal appointment of guardians for children based on Decision Number: 87/Pdt.P/2021/PN Tjk?. The research method uses a normative and empirical juridical approach. The type of data used is secondary data and primary data. Collecting data through library research and field research. Analysis of the data used is qualitative juridical.